Time to replace the spherical equivalent with the average paraxial lens power - Kaye, Stephen B (BMJ open ophthalmology, 2023)
While for the ApP , the average is the average of orthogonal and oblique paraxial rays, that is, ApP =average orthogonal and oblique paraxial power F¯ApP(orthogonal+oblique), F¯ApP(orthogonal+oblique)=C14+C14+C2−C14, ApP=F¯ApP(orthogonal+oblique)=C14+C24. [...]the ApP is equal to half the SE if calculated in cross cylinder form, that is, ApP=SE2. If a refractive error, however, does comprise a true spherical component, then the average of that component is of course the sphere. [...]for a refractive power that contains a sphere, the ApP=Sphere+C4 and the SE=Sphere+C2 and the difference between the ApP and SE is equal to C4 . The ApP as a scalar measure is more inclusive and appears to be associated with better visual acuity than the SE, although further clinical trials are needed particularly in different age groups and conditions.